Industrial Activities vs Agricultural Activities in the Profile of the Regions of the Republic of Moldova - Ina Mogildea; Maria Magdalena Turek Rahoveanu (Journal of Agriculture and Rural Development Studies, 2024)
The study analyses the development of non-agricultural activities in the Republic of Moldova, a region characterized by the strong influence of a polarizing zone, due to the convergence of current and historical socio-economic relations. Urban areas were chosen to develop the methodology for determining the role of non-agricultural activities in regional development. The study proposes to emphasize the polarization potential of some rural regions, to bring to the influence of predominantly urban regions. The non-agricultural rural economy provides the theoretical framework for this analysis, which investigates the complexity of non-agricultural activities. The case study highlights how the urban area polarizes the labour force from the nearby rural area.